Peningkatan Keaktifan Dan Kemampuan Pemecahan Masalah Pada Pembelajaran Matematika Melalui Metode Inquiry Terbimbing(Ptk Pada Siswa Kelas VII A Semester II SMP Negeri 2 Sawit Boyolali Tahun 2014/2015) - Darmawan, Adi, Drs. Ariyanto, M.Pd (2015)
The purpose of this research is to improve the liveliness and problem solving skills in mathematics classroom learning VII A SMP Negeri 2 Sawit through the application of guided inquiry method. This study includes classroom action research. VII A grade students as subjects of action receiver and giver math teacher as the subject of action. Data collection method used is the method of observation, field notes, interview, test, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion. Results of the study is to show an increase in activity and problem solving skills in the learning of mathematics problem solving. An increase in the activity can be seen from the 1) active students to ask questions of (16.67%) increased to (73.33%) 2) activeness in the expression of (10%) increased to (66.67%), 3) liveliness in a discussion group of (20%) increased to (73.33%). There is an increasing problem-solving skills can be seen from 1) Students are able to understand the problems of (20%) increased to (76.67%), 2) Students are able to plan the completion of (13.33%) increased to (70%), 3) Students are able to carry out the settlement of the problem according to plan (16.67%) increased to (66.67%), 4) Students are able to check back for all the steps of (13.33%) increased to (63.33 %). So it can be concluded that the application of guided inquiry method can enhance the activity and problem solving skills in mathematics.